Investigation of the Thermal Improvement and the Kinetic Analysis of the Enriched Coal - Selma Duzyol; Cem Sensogut (Journal of Combustion)
The present research work is comprised of three main parts. The first part is about the enrichment of lignite coal by the utilization of dense medium separation called float and sink method. The second part deals with the investigation of the thermal behaviour for the coals enriched while the last part is concerned with the kinetic analysis of the coal combustion. The float and sink method is the mostly used technique for low-rank coal beneficiation in coal preparation plants of Turkey. In order to realize this process, the coal samples were, at first, fractioned to five different sizes which were -32+25 mm, -25+16 mm, -16+8 mm, -8+4.75 mm, and -4.75+2 mm. Each fraction was, then, processed in the dense mediums with the specific gravities of 1.20, 1.30, 1.40, 1.50, and 1.60 g/cm3, respectively. The thermal behaviour of the floated materials from the float and sink process was investigated in detail with the thermogravimetric analysis (TG) and the differential thermogravimetric analysis (DTG). The ignition and peak temperatures for the samples were also ascertained and correlated with the float and sink test results. In the final part of the study, the kinetic analysis of the coal samples was carried out by the Coats–Redfern method and the activation energies of the enriched coals were determined. The activation energies of the raw and the enriched coals were assessed and compared. The calculated activation energy values for the combustion reactions of the coal samples ranged were found to be between 15.17 kJ/mol and 97.45 kJ/mol. The strong correlation was obtained between the float and sink test results especially with the ash content of the coal samples and the combustible characteristic of the floated materials such as ignition temperatures, peak temperatures, and activation energies. The combustion characteristics of the coal samples were resultantly ascertained to be very dependent on the coal structure.